The language of science - Reeves, Carol (London ; New York : Routledge, 2005)
With more and more scientific language being applied -and misapplied- in our daily lives, this title from the Intertext series explores the use of scientific terms through hot topics from the MMR vaccine to AIDS and biological weapons
Language -- Metaphor in science -- The grammar of science -- Language, discourse and facts -- Understanding the rhetorical in science -- Science and culture : the interaction of discourses -- Science and society
Includes bibliographical references and index
Print version record
eBooks on EBSCOhost
Keywords: Communication in science; Science -- Language; Technical writing; Information scientifique; Sciences -- Langage; Rédaction technique; technical writing; LANGUAGE ARTS & DISCIPLINES -- Rhetoric; REFERENCE -- Writing Skills; LANGUAGE ARTS & DISCIPLINES -- Composition & Creative Writing; Communication in science; Science -- Language; Technical writing